A new subspecies of Pulmonaria officinalis (Boraginaceae) from the southern Alps - Astuti, Giovanni; Cristofolini, Giovanni; Peruzzi, Lorenzo; Pupillo, Paolo (Phytotaxa, 2014)
Populations of Pulmonaria with unique features associated with shady and dry conditions were found in high beech woods on the west side of Mt. Marzola and in other dolomitic sites of Trentino (southern Italian Alps). Morpho-statistical and karyological analyses suggest that these populations represent a new subspecies of P. officinalis, Pulmonaria officinalis subsp. marzolae. The change of the basal leaf shape during the year, peculiar traits of foliar spots and hairs as well as a divergence of the karyotype asymmetry parameters suggest that this taxon is distinct from the typical form of P. officinalis. General form, the major hair types, inflorescence morphology and the chromosome number 2n = 16, however, suggest its affinity to this species.